Virological Features of Hepatitis C Virus in Hemodialysis Patients : Northern Districts of Palestine - Fekri Helmi Samarah (My University, 2001)
A total of 71 HD patients were followed up with respect to HCV markers for 18 months. Initial findings showed that 37 (52.11%) were HCV positive and 12 (16.9%) were HBV positive. By the end of the first period (6 months), the prevalence of HCV increased to 65.15 % as 6 new cases became HCV positive. With respect to HBV the prevalence dropped to 10.61 %. ALT levels were monitored on a weekly basis as an indicator for episodes of HCV infection. This marker strongly correlates with HCV infection as all seroconverted HCV new cases showed clear ALT elevation in the acute phase of infection. Fluctuation in ALT levels among HBV positive cases were not as clear as for those with HCV infection, however, HBV positive cases seem to exhibit constantly high levels. Such fluctuations were also observed among some of the initially HCV positive cases, indicating possible HCV re-infection among such cases. Preliminary evidence suggests that a nosocomial infection was behind the observed increase in the prevalence rate of HCV. By the end of this period 5 HCV negative and 1 HCV positive subject died due to various complications. During the second phase of the study, non-of the HCV negative cases (41) were seroconverted to HCV positive and only 1 case was seroconverted to HBV positive. ALT elevation was observed among 2 HCV negative cases, however, non-of these 2 cases entered the acute phase of infection to either HCV or HBV infections. Strict hygienic conditions based on the recommendations of this study is more likely behind the limited number of newly infected cases. By the end of this phase 2 of the HCV positive cases and 7 of the HCV negative died. During the third phase HCV seroconversion was observed in 1 case out of initially 40 HCV negative cases involved. None of the 80 cases involved at the beginning of this phase was seroconverted to HBV positive. Out of the 40 HCV negative cases, 5 died, 1 of which was HBV positive. Out of HCV positive cases involved in this phase (40), 5 patients died and 2 of them were with dual infection (HC V/HB V). All HCV seroconverted cases (7 cases) clearly showed a strong association between high ALT levels and the acute phase of infection. Incubation period ranged between 21-109 days, based upon the findings of high ALT levels in two successive samples and the appearance of either anti-core or anti-NS antibodies. Anti-core antibodies seem to appear in an earlier time compared to anti-NS antibodies as 4 of the seroconverted cases expressed anti-core antibodies as early as 21 days and up to 30 days. The production of an antibody response to the NS antigen occurs relatively late (56109) days. ALT elevation was found to be associated with both antibodies in the acute phase of infection. Subjects expressing anti-NS seem to show much higher ALT levels, that last for longer time. Infection rates increased dramatically with duration of dialysis, thus confirming of the role of dialysis as a risk factor for HCV infection. With increased duration of infection a shift from NS or core to both markers was also observed.

لقد تمت دراسة ومتابعة مدى تطور وانتشار مرض التهاب الكبد الوبائي الفيروسيC على 71 مريضا ممن يتابعون عملية الغسيل الكلوي في المستشفى الوطني – نابلس. لقد بينت الدراسة الأولية أن 37 مريضا أي ما يعادل حوالي 52% من المرضى في هذه الوحدة من المصابين بهذا المرض في حين كان12 مريضاً أي ما يعادل 17% من المصابين بالتهاب الكبد الفيروسي. لقد أجريت الدراسة على ثلاث فترات زمنية متلاحقة كل فترة منها ستة شهور، نظرا لمتغيرات عدة أهمها التحاق مرضى جدد وموت آخرين مما تسبب في عدم ثبات أعداد عينة الدراسة ومما استدعى لزيادة فترة المتابعة ومع نهاية الفترة الأولى لوحظ زيادة في نسبة الإصابة بالتهاب الكبد الفيروسي C، حيث وصلت النسبة إلى 65.15% حيث انضم ستة مرضى جدد إلى قائمة المصابين، في حين لوحظ انخفاض في نسبة الإصابة بالتهاب الكبد الفيروسي B، حيث انخفضت النسبة من حوالي 17% إلى 10.61% وكانت العدوى المزدوجة وأصابه هؤلاء المرضى بالفيروس C هي السبب في هذا الانخفاض. وقد تم استخدام الانزيم ALT المفرز من الكبد كمقياس ومؤشر للإصابة حيث تمت دراسة مستويات الأنزيم بشكل أسبوعي، وقد دلت الدراسات على أن هذا المؤشر مرتبط بشكل كبير مع الإصابة بالالتهاب الفيروسي C. وقد بينت الدراسة مثل هذا التوافق حيث لوحظ ارتفاع حاد في مستوى الإنزيم لدى جميع المرضى الذين أصيبوا خلال الفترة الأولى من الدراسة، كما لوحظت ذبذبات في مستوى الأنزيم لدى المرضى الذين كانوا مصابين أصلا بهذا الفيروس مما يؤكد على إمكانية تكرار حدوث العدوى، وتشير النتائج الأولية إلى أن العدوى من داخل الوحدة هي السبب الرئيسي وراء هذه الإصابات والمسؤولة عن الزيادة في نسبة الإصابة بالالتهاب الفيروسيC، ومع نهاية هذه الفترة لوحظ وفاة ستة مرضى لأسباب وتعقيدات فسيولوجية مختلفة، كان من بينهم أحد المصابين بالتهاب الكبد الفيروسيC . خلال فترة الدراسة الثانية لم تسجل أية اصابة جديدة بالتهاب الكبد الفيروسي C من بين 41 حالة سالبة، في حين سجلت إصابة واحدة بالتهاب الكبد الفيروسي B، كما لوحظت ارتفاعات حادة في مستوى الأنزيم alt لدى مريضين ولم يلاحظ دخول أي من هذين المريضين في الأعراض الحادة للالتهاب الفيروسي B أو C، ويبدو أن ظروف الرقابة الصحية المشددة والتي استخدمت في الوحدة بناء على نتائج وتوصيات المرحلة الأولى من هذه الدراسة كانت وراء الحد من انتشار المرض وعدم تسجيل أية اصابة جديدة، وقد توفي في نهاية هذه الفترة تسعة مرضى كان من بينهم اثنين من المصابين بالتهاب الكبد الفيروسي. أما في المرحلة الثالثة فقد لوحظ حالة عدوى جديدة بالتهاب الكبد الفيروسي C من بين 40 حالة سالبة تضمنتها هذه المرحلة، ولم تسجل أي اصابة بالتهاب الكبد الفيروسي .B ومع نهاية الفترة الثالثة توفي 10 مرضى من أصل 80 مريضا. (40 حالة مصابة HCV و 40 حالة غير مصابة) كان من بينهم ثلاثة مرضى من المصابين بالتهاب الكبد الفيروسي. وتشير النتائج السريرية بأن الحالات السبع التي أصيبت خلال فترات الدراسة الثلاث إلى وجود علاقة قوية تربط بين الإنزيم ALT مع الطور المرضي للعدوى، حيث لوحظ ارتفاع في مستوى الأنزيم ALT لدى جميع الحالات المصابة حديثا. أما فيما يتعلق بفترة حضانة الفيروس HCV فقد تراوحت ما بين (21- 109) أيام اعتماداً على ارتفاع مستوى الأنزيم ALT في قراءتين متتاليتين متزامنا مع ظهور الأجسام المضادة لكل من انتجن NS و أنتجن Core في العينات المصابة. وقد لوحظ أن الأجسام المضادة لأنتجن NS تظهر مبكراً مقارنة مع الأجسام المضادة لأنتجن NCولوحظ كذلك بأن الارتفاع في مستوى الأنزيم ALT كان مرتبطا بكلا النوعين من المضادات الحيوية في الطور الحاد من المرض، مع ارتفاع أعلى في مستوى الأنزيم لدى المرضى الذين ظهرت لديهم المضادات الحيوية لأنتجن NS. أما فيما يتعلق بنسبة الإصابة فقد لوحظ زيادة مطردة مع ازدياد فترة الغسيل الكلوي مما يؤكد أن مثل هذه العملية تعتبر من العوامل الخطرة والمسببة لانتقال المرض (HVC) كذلك ومع ازدياد فترة الغسيل هنالك انتقال من نمط المضادات الحيوية للأنتيجن NS أوCore إلى كلا المؤشرين.
Virological Features of Hepatitis C Virus in Hemodialysis Patients : Northern Districts of Palestine